2007
DOI: 10.1086/522010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Humoral Responses to Influenza in Gabonese Children Living in Rural and Semi‐Urban Areas

Abstract: Background. With the current attention to the pandemic threat of avian influenza viruses, it is recognized that there is little information on influenza in Africa. In addition, the effects of influenza vaccination in African countries could be very different from the effects in regions with less exposure to microorganisms and parasites.Methods. To monitor the presence of influenza viruses and investigate the immunological responses to influenza vaccination, schoolchildren in semi-urban and rural regions of Gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The presence of helminth infections, frequent in rural areas of those countries, has been associated with weak response to BCG vaccine in tropical countries [56]. Similar observation with influenza vaccine was reported in children living in rural regions of Gabon [57]. Antiviral agents have been used in the treatment of influenza, but only rarely in TSTCs [6 ,17 ,18,55,58].…”
Section: Prophylaxis and Treatment Of Influenza Infectionsmentioning
confidence: 84%
“…The presence of helminth infections, frequent in rural areas of those countries, has been associated with weak response to BCG vaccine in tropical countries [56]. Similar observation with influenza vaccine was reported in children living in rural regions of Gabon [57]. Antiviral agents have been used in the treatment of influenza, but only rarely in TSTCs [6 ,17 ,18,55,58].…”
Section: Prophylaxis and Treatment Of Influenza Infectionsmentioning
confidence: 84%
“…This study (registered at ClinicalTrials.gov under registration number NCT01192802) was designed as a single-center, randomized, controlled, assessor-blinded clinical trial to compare the efficacy and safety of an albendazole single-dose with a two-or three-dose regimen in school-age children residing in an In this region, soil-transmitted helminths (5,16,19), malaria, and schistosomiasis (19,21,(27)(28)(29) are endemic. Approximately 3,000 inhabitants reside in these villages, and houses typically have poor sanitation.…”
Section: Methodsmentioning
confidence: 99%
“…These infections are responsible for significant morbidity, which includes anemia (7,8), stunting (9), and iron and vitamin A deficiencies (10)(11)(12)(13). Additionally, helminth infections have the capacity to reduce the host immune response to vaccines as well as to environmental and parasitic antigens (14)(15)(16). The consequences of such hyporesponsiveness may explain changes in host susceptibility to commonly encountered pathogens, as reported recently (17)(18)(19).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…However, sporadic reports from the Gambia [6], Senegal [7], Congo [8], Madagascar [8], Kenya [9], Ivory Coast [10], and from Gabon [11], have indicated that influenza is circulating and may be causing epidemics regularly. The study in Gabon recorded extremely high levels of antibodies to influenza A H3N2 virus in schoolchildren [11]. The haemagglutination inhibition (HI) antibodies to this influenza A virus at titers of 1,530 (ranging from 80 to 17,920) indicated that the virus had been circulating within the community in the recent past.…”
Section: How Little We Knowmentioning
confidence: 99%